Avian Influenza (H5N1) Bentuk Pernafasan Pada Entok (Cairina moschata) Sehat Di Yogyakarta - Hastari Wuryastuti; Wasito Wasito (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Influenza virus type A H5N1 has become epidemic in poultry population in Indonesia and has been suspected sporadically to cross humans. All the available evidences suggest that the most common primary introduction of AI viruses into an area is by wild birds. The ducks form the reservoir of influenza type A viruses in nature and may spread AI virus from farm to farm by mainly mechanical transfer of infective feces, in which AIvirus may be present at high concentrations and may survive for considerable periods. In the present paper, we report on the immunohistochemical and molecular investigations performed on nine ducks (Cairina moschata)naturally infected by influenza virus type A. The H5N1 gene was detected by molecular analysis of the reversetranscriptase-polymerase chain reaction in the parenchyma of the lungs, but neither in the pancreas nor the intestines. Immunohistochemical streptavidin biotin assay of monoclonal antibody anti nucleoprotein viral antigen also only corresponded to virus location within the vascular endothelia of the lung only. Our findings may suggest that the ducks provide an environment transmission of AI virus not only by a fecal route, but also by either an airborne route or direct contact with contaminated respiratory secretions. Moreover, we suggest that surveillance activities influenza viruses of the avian origin are critical for characterizing AI virus in the ducksand requires a high level of preparedness.Keywords: ducks, immunohistochemical, molecular, monoclonal antibody, airborne route